2005
DOI: 10.1523/jneurosci.3051-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activin Induces Tactile Allodynia and Increases Calcitonin Gene-Related Peptide after Peripheral Inflammation

Abstract: Calcitonin gene-related peptide (CGRP) is a sensory neuropeptide important in inflammatory pain that conveys pain information centrally and dilates blood vessels peripherally. Previous studies indicate that activin A increases CGRP-immunoreactive (IR) sensory neurons in vitro, and following wound, activin A protein increases in the skin and more neurons have detectable CGRP expression in the innervating dorsal root ganglion (DRG). These data suggest some adult sensory neurons respond to activin A or other targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 75 publications
5
54
2
Order By: Relevance
“…In support of our proposal that TGF-␤1 plays a positive role in inflammation-induced hyperalgesia, activin A, another member of the TGF-␤ family, is released during peripheral inflammation. This increases the expression of the calcitonin generelated peptide and pain sensation (49). In addition, it was found that activin A mediates hyperalgesia through a mechanism involving acute sensitization of TRPV1 (50).…”
Section: ␤1mentioning
confidence: 99%
“…In support of our proposal that TGF-␤1 plays a positive role in inflammation-induced hyperalgesia, activin A, another member of the TGF-␤ family, is released during peripheral inflammation. This increases the expression of the calcitonin generelated peptide and pain sensation (49). In addition, it was found that activin A mediates hyperalgesia through a mechanism involving acute sensitization of TRPV1 (50).…”
Section: ␤1mentioning
confidence: 99%
“…To investigate increase in CGRP release during tumor growth, we determined the mRNA levels of pro-CGRP, a precursor of CGRP, in DRGs (L 1-5 ) in tumorbearing WT because CGRP was reported to be up-regulated, and the pro-CGRP mRNA levels in the DRGs rose in the case of peripheral inflammation (24,25). As Fig.…”
Section: Effects Of Sciatic Nerve Denervation On Pro-cgrp Mrna Levels Inmentioning
confidence: 99%
“…These findings suggested that tumor implantation up-regulated pro-CGRP in the DRGs innervating the area of implantation and increased CGRP release and that CGRP was synthesized in the neuronal systems and was delivered to the periphery of the nerves innervating the sites where tumors grow. When inflammation was induced, CGRP was reported to be up-regulated, and the pro-CGRP mRNA levels in the DRGs that innervate the sites of inflammation rose (24,25). This may have been caused by the increased release of CGRP that was stimulated by the implanted tumors.…”
Section: Effects Of Sciatic Nerve Denervation On Pro-cgrp Mrna Levels Inmentioning
confidence: 99%
“…Each trial was repeated five times at 4 min intervals, and the PWL is the average of the five responses. Responses to mechanical stimulation in mice were assessed using calibrated von Frey filaments using the up-down paradigm as previously performed for assessment of tactile allodynia in rats (Xu et al, 2005).…”
Section: Behavioral Assays Of Thermal Hyperalgesia and Tactile Allodymentioning
confidence: 99%
“…Recent evidence suggests that activin itself causes both acute and prolonged tactile allodynia in vivo (Xu et al, 2005). Activin has been shown to increase expression of calcitonin-gene related peptide (CGRP) (Ai et al, 1999;Cruise et al, 2004), a peptide marker of the major subset of peripheral nociceptors that may contribute to the prolonged phase of hyperalgesia (Urban et al, 1994).…”
Section: Introductionmentioning
confidence: 99%